2020
DOI: 10.1002/adma.202006201
|View full text |Cite
|
Sign up to set email alerts
|

A Monochloro Copper Phthalocyanine Memristor with High‐Temperature Resilience for Electronic Synapse Applications

Abstract: Memristors are considered to be one of the most promising device concepts for neuromorphic computing, in particular thanks to their highly tunable resistive states. To realize neuromorphic computing architectures, the assembly of large memristive crossbar arrays is necessary, but is often accompanied by severe heat dispassion. Organic materials can be tailored with on‐demand electronic properties in the context of neuromorphic applications. However, such materials are more susceptible to heat, and detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 75 publications
0
46
0
Order By: Relevance
“…Moreover, organic materials have attracted much attention because of the advantages of low cost, lightweight, strong scalability, and good biodegradability. , Recently, some memristors based on organic 2D materials with reliable RS behaviors have been demonstrated. , Compared with inorganic materials, organic and its hybrid materials have the characteristics of low cost, high flexibility, biocompatibility, etc., ,, which have more potential for the application of wearable electronic products and biological neural networks. Through molecular design and functional group regulation, the properties of organic materials can be further improved and enriched, which also greatly improves the realization of information processing and storage and synaptic applications based on organic 2D memristors …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, organic materials have attracted much attention because of the advantages of low cost, lightweight, strong scalability, and good biodegradability. , Recently, some memristors based on organic 2D materials with reliable RS behaviors have been demonstrated. , Compared with inorganic materials, organic and its hybrid materials have the characteristics of low cost, high flexibility, biocompatibility, etc., ,, which have more potential for the application of wearable electronic products and biological neural networks. Through molecular design and functional group regulation, the properties of organic materials can be further improved and enriched, which also greatly improves the realization of information processing and storage and synaptic applications based on organic 2D memristors …”
Section: Introductionmentioning
confidence: 99%
“…Recently, as shown in Figures 2G,J. Zhou et al reported a highly chemically and thermally stable flexible memristive array by using monochloro copper phthalocyanine (ClCuPc) materials (Zhou et al, 2021). Benefitting from the intrinsic high thermal stability of CuPc and the further improvement of air stability caused by chlorination, the fabricated memristive device could exhibit reliable resistive switching behavior at 300 °C.…”
Section: Flexible Organic Memristive Arraysmentioning
confidence: 99%
“…In addition, the implementation of large-scale memristive arrays leads to inevitable heat dissipation, which further affects the reliability and stability of organic materials. Among various organic materials, copper phthalocyanines have been intensively explored due to their reliable chemical and thermal stability (Choi et al, 2008;Lv et al, 2019;Wang et al, 2016b;Wang et al, 2017;Zhou et al, 2021). Recently, as shown in Figures 2G,J.…”
Section: Flexible Organic Memristive Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the intrinsic advantages in optical properties, the significant progress of organic solids in charge transport lead to the promising practical applications of their electronic devices represented by organic field-effect transistor (OFET), including OFET memories in integrated circuits and portable and wearable electronic devices, for example, radio-frequency identification tags, sensor arrays [4] and neuromorphic applications. [5] Nevertheless, based on molecular materials, one of the fascinating challenges is realizing a composite structure or device-based function through single molecules. [6] Actually, single molecules or single-molecule monolayers were constructed to investigate their charge transport characteristics and demonstrate their transistor and rectification behaviors, namely "unimolecular electronics (UME)".…”
mentioning
confidence: 99%